2016
DOI: 10.1186/s40246-016-0067-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of six CpG-SNPs in the inflammation-related genes with coronary heart disease

Abstract: BackgroundChronic inflammation has been widely considered to be the major risk factor of coronary heart disease (CHD). The goal of our study was to explore the possible association with CHD for inflammation-related single nucleotide polymorphisms (SNPs) involved in cytosine-phosphate-guanine (CpG) dinucleotides. A total of 784 CHD patients and 739 non-CHD controls were recruited from Zhejiang Province, China. Using the Sequenom MassARRAY platform, we measured the genotypes of six inflammation-related CpG-SNPs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…The expression at the fork or bend is significantly lower than the vertical. SNPs are DNA sequence polymorphisms caused by mutations at the genomic nucleotide level, including single base transformations, transversions, and single base deletions and insertions . The susceptibility may be related to race, genetic, environmental, or other factors such as age, sex, diet, and smoking.…”
Section: Discussionmentioning
confidence: 99%
“…The expression at the fork or bend is significantly lower than the vertical. SNPs are DNA sequence polymorphisms caused by mutations at the genomic nucleotide level, including single base transformations, transversions, and single base deletions and insertions . The susceptibility may be related to race, genetic, environmental, or other factors such as age, sex, diet, and smoking.…”
Section: Discussionmentioning
confidence: 99%
“…17 Of the 10 cases driving this shared region (Table S4), the seven with available diagnostic data had depression (5/7), anxiety (3/7), and alcohol dependence (3/7). Two cases had multiple psychiatric diagnoses, and four cases had previous documented attempts.…”
Section: Discussionmentioning
confidence: 99%
“…A 5′-UTR variant (rs9395208) might not be associated with Lp-PLA2 activity and mass in the Chinese population, 92 but in the same population, another study found the minor allele of rs9395208 to be a protective factor for CHD (OR = 0.78, 95% CI: 0.62-0.98, P = .03). 115 However, Grallert et al 90 established that this variant was significantly associated with Lp-PLA2 mass but not with activity or prevalence of CHD or CAD in participants of European ancestry.…”
Section: Other Snpsmentioning
confidence: 99%